The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/978-3-030-47073-9_3-1
|View full text |Cite
|
Sign up to set email alerts
|

Vocabulary Development in Early Language Education

Abstract: Building lexical knowledge is one of the most fundamental developments in early childhood; as such development is associated with children's later academic achievement and other language abilities. Both breadth (e.g., receptive vocabulary size) and depth (e.g., syntagmatic and paradigmatic knowledge) of lexical knowledge are vital, as the former indicates how much children know and the latter indicates how well they know it. Therefore, it would be crucial for any language program to provide qualified teaching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 77 publications
1
2
0
Order By: Relevance
“…The results of the study are in line with Sun and Yin (2020) who argue that technology can positively enhance YLL's learning. Regarding the four themes they found in their literature review (i.e., (1) lack of research from non-US contexts, (2) lack of information about instruction principles and amount of instruction, (3) lack of research on children's vocabulary depth, and (4) lack of better understanding on the role of socioeconomic status), the current study covered the first two themes in…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The results of the study are in line with Sun and Yin (2020) who argue that technology can positively enhance YLL's learning. Regarding the four themes they found in their literature review (i.e., (1) lack of research from non-US contexts, (2) lack of information about instruction principles and amount of instruction, (3) lack of research on children's vocabulary depth, and (4) lack of better understanding on the role of socioeconomic status), the current study covered the first two themes in…”
Section: Discussionsupporting
confidence: 87%
“…Align with the growth of theory and research on YLLs, research has examined YLL's vocabulary learning. For example, in their review paper on YLL's bilingual vocabulary learning, Sun and Yin (2020) identified 15 studies that have explored vocabulary development among preschool children. Synthesis of the studies indicated several themes among the study including (1) lack of research from non-US contexts, (2) lack of information about instruction principles and amount of instruction, (3) lack of research on children's vocabulary depth, and (4) lack of better understanding on the role of socioeconomic status.…”
Section: Young Language Learners and Vocabulary Learningmentioning
confidence: 99%
See 1 more Smart Citation